2016
DOI: 10.1371/journal.pone.0168798
|View full text |Cite
|
Sign up to set email alerts
|

Is Adjuvant Cellular Immunotherapy Essential after TACE-Predominant Minimally-Invasive Treatment for Hepatocellular Carcinoma? A Systematic Meta-Analysis of Studies Including 1774 Patients

Abstract: PurposeCellular immunotherapy has appeared to be a promising modality for the treatment of malignant tumor. The objective of this study was to evaluate the efficacy of cellular immunotherapy combined with minimally invasive therapy.MethodsWe searched PubMed, Web of Science and The Cochrane Library through March 2016 for relevant studies. Short-term efficacy (the disease control rate, the control rate of quality life and the AFP descent rate) and long-term efficacy (overall survival (OS) and progression-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Moreover, in contrast to those previous systematic reviews [20,21], our data found adjuvant AIT significantly reduced the rate of mortality and tumor recurrence for such patients. Our results were confirmed by other meta-analysis that AIT was a feasible adjuvant treatment for the improvement of the clinical outcomes for HCC patients after minimally invasive treatment [46]. …”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in contrast to those previous systematic reviews [20,21], our data found adjuvant AIT significantly reduced the rate of mortality and tumor recurrence for such patients. Our results were confirmed by other meta-analysis that AIT was a feasible adjuvant treatment for the improvement of the clinical outcomes for HCC patients after minimally invasive treatment [46]. …”
Section: Discussionsupporting
confidence: 87%
“…In light of previous studies, mitochondrial oxidative stress is regarded as the dominant cellular event in APAP-induced acute hepatotoxicity (Wang et al., 2016a; Yan et al., 2018). Several natural compounds have been reported to protect against APAP-induced acute liver injury via antioxidant capacity (Rasool et al., 2010; Ding et al., 2016; Rashid et al., 2016). In our study, tempol treatment upregulated levels of antioxidant proteins, including SOD, catalase and GSH, thus inhibiting oxidative stress in APAP-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The results verified that vaccination of mice with the novel HSP70-P/AFP-P vaccine mounted strong natural killer cell and CD8 + T cell responses, inducing a protective effect against AFP-producing tumors in mice [ 68 ]. A systemic meta-analysis indicated that cellular immunotherapy was a feasible adjuvant treatment that could be beneficial for the improvement of short-term response and long-term survival of HCC patients after minimally invasive treatment [ 76 ]. Recently, clinical trials showed that nivolumab, a programmed cell death protein-1 (PD-1) immune checkpoint inhibitor, produced durable objective responses for treatment of HCC, indicating the possibility of combining nivolumab with AFP to suppress the proliferation of cancer cells [ 77 ].…”
Section: Application Of Afp In the Immunotherapy Of Hepatocellularmentioning
confidence: 99%